Uporaba integralnega geografskega modela raziskovanja okolja in okoljskih sestavin za varovanje vodnih virov - Prah, Klemen (Geografski vestnik, 2007)
We used the integral model of geographical study of the environment and its components as a basis of our river basin study, with the purpose of informing the public and environment decision makers about the importance of preserving good condition of water resources. The methodology, which is based on the study of mutual correlation between natural characteristics of the river basin, the activities in the river basin and the quality of water, includes the hydrogeographical study of the river basin, the establishment of environmental indicators for the protection of the river basin, and the foundation of ten research points for monitoring the condition of water resources. We chose the Sotla's river basin for our study, but the model can also be transferred to other river basins.
Keywords: vodni viri; drainage basin; porečje; hidrogeografija; varstvo voda; varstvo okolja; environmental protection; modeli; Slovenia; Slovenija; Sotla; Sutla